Exploring Tertiary Level ESL Students’ Perspectives of Using Self-Assessment for Academic Writing: A Conceptual Paper - Ravana, Venosha; Taib, Roslizawati; Junit, Juliazilah (Development in Language Studies, 2023)
Critical thinking in academic writing allows students to present evidence, arguments and conclusions clearly. It also promotes deeper, creative and reflective insights on various matters using the medium of writing. However, Malaysian tertiary level ESL learners have been found to struggle with writing critically for academic purposes. This conceptual paper presents a reflective learning tool, a weekly self-assessment, that has been theorized to help ESL learners to reflect on their academic writing practices and improve on their weaknesses when it comes to writing critically. The methodology proposed is an exploratory qualitative study using thematic analysis and document analysis on semi-structured interviews and students’ written assignments respectively. It is hoped that this paper can provide directions for practitioners looking to incorporate critical thinking via reflective learning practices in ESL classrooms.